The Increase of Arthropods Biodiversity in Paddy Field Ecosystem Managed by Using Integrated Pest Management at South Borneo - Samharinto Samharinto; Abdul Latief Abadi; Bambang Tri Raharjo; Hakimah Halim (Journal of Tropical Life Science, 2012)
We have studied the arthropods biodiversity in two paddy field ecosystems, namely, paddy field ecosystem using Integrated Pest Management (IPM) system and non-IPM paddy field ecosystem. This study was conducted from April 2011 - November 2011 in three locations, that is, Pasar Kamis village and Sungai Rangas village in Banjar regency, and Guntung Payung village in Banjarbaru city, South Borneo Province. In this study, we used insect nets, yellow sticky traps, light trap and pitfall trap to get the sample or catch the arthropods in one period of planting season. The arthropods caught were then classified into some classes: pest (herbivore), natural enemy (parasitoid and predator), and other arthropods. After that, the Species Diversity Index was determined using its Shannon-Wiener Index (H), Evenness (e), Species Richness (R), and Species Similarity Index (IS). The sum of arthropods which have the characteristic of pest and parasitoid were higher in the IPM paddy fields than in the non-IPM paddy fields, and the sum of other arthropods were the same. The highest H and e values were in the IPM paddy field in Pasar Kamis village. The IS value for each three locations were 77.5% in Pasar Kamis village, 93.42% in Guntung Payung village, and 78.76% in Sungai Rangas village.Keywords: diversity, arthropods, ecosystem, and SLPHT